PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT MENTARI BOOKS STORE BRANCH MERUYA UTARA JAKARTA BARAT - Oky Suwardi; Dewi Sartika (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Employee performance is an important factor for organizations that seek to maintain service quality and operational effectiveness. This study aims to analyze the effect of work discipline and physical work environment on employee performance at PT Mentari Books Store Branch Meruya Utara, West Jakarta. The research used a quantitative associative approach with saturated sampling involving 70 employees. Data were collected using a Likert-scale questionnaire and analyzed using SPSS 27 through validity, reliability, classical assumption, simple regression, multiple regression, correlation, determination, t-test, and F-test procedures. The findings indicate that work discipline has a strong and significant relationship with employee performance, while the physical work environment also contributes positively to employee performance. Simultaneously, work discipline and physical work environment explain 81.7% of the variation in employee performance, indicating a strong combined effect. The results imply that improving punctuality, rule compliance, workplace facilities, and physical comfort can strengthen employee performance and support human resource management practices in retail-based educational service companies.